Otimização Multi-Objetivo de WAMS Resilientes para a Estimação de Estado - Cruz, Marco António do Rosário Santos (2021)
This research project aims to present a new PMU(Phasor Measurement Units) Optimal Allocation algorithm in a power transmission network with multiple objectives. Planning a measurement system in WAMS (Wide Area Measurement System) requires technical and economic criteria for a better decision by the operators of such systems. Many Optimal PMU Placement (OPP) algorithms have been presented in the literature, motivated by minimizing costs with PMUs and with communications, but also to meet technical criteria, such as analytical or numerical observability, measurement robustness, signal stability, among others. Some works in the literature have formulated the OPP problem as a multi-objective problem and some solutions were presented given the relevant decision factors involved in designing a good planning system for WAMS. A relevant combination of objectives is the trade-off that has to exist between the investment cost and the desired or necessary robustness of a measurement plan in a given context. The robustness of a measurement system is directly related to the State Estimation (SE) function, which is fundamental in the operation and monitoring of a Power Systems Control Center. A reliable SE depends on a good measurement plan. However, the operator has limited financial availability and has to face the dilemma of determining the appropriate measurement plan, even in the face of budget constraints. This work aims to respond to this dilemma, as it seeks to formulate the problem with clear objectives to achieve robustness in the measurement plan and minimize total costs. Thus, it is proposed an algorithm that uses numerical observability to characterize this robustness and also the graph theory to formulate the problem of total costs, which considers practical and more realistic aspects of the installation of PMUs as well as addressing costs of communication infrastructures. In the end, a set of optimal solutions is built that, in a real situation, would serve better for judicious decision by the planners of the measurement system.